Trade liberalisation, adoption costs, and import margins in CEEC and OECD trade - Richard Frensch (Osteuropa-Institut Regensburg, 2008)
Within a standard gravity framework I explore the impact of country size and trade liberalisation on extensive and intensive margins of imports across broad categories of goods. This allows testing hypotheses from two distinct strands of the trade literature, i.e., vertical integration versus trade in technology goods. First, there is evidence in favour of a unilateral complement to Yi's (2003) claim that vertical integration magnifies the trade effect of multilateral trade liberalisation: I find a substantially stronger than average impact of unilateral trade liberalisation on imports of vertically integrated intermediate goods along both extensive and intensive margins. On the contrary, I find no evidence in favour of Romer's (1994) hypothesis of fixed costs of technology adoption when the state of technology is operationalised as the variety of capital goods. Results are robust to the measurement of trade liberalisation, to extending the product space allowing for national product differentiation, to sample composition, and to varying the gravity framework according to Baldwin and Taglioni (2006).
Keywords: F12; F14; O33; 330; Gravity; product variety; vertical integration; technology adoption; Außenhandelsliberalisierung; Landesgröße; Importhandel; Handelsspanne; Technologietransfer; Innovationsdiffusion; Kosten; Gravitationsmodell; EU-Staaten (Osteuropa); OECD-Staaten